Campos elétricos transversais sobre nanotubos de carbono: um estudo de primeiros princípios - Silva, Leandro Barros da (2008)
In this Thesis we studied through first principles methods the effects of uniform transversal electric fields on the structural and electronic properties of carbon nanotubes. We study the formation of Si-doped carbon nanotubes through the interaction of Si with single-vacant nanotubes and investigate the action of electric fields on semiconducting and metallic carbon nanotubes, both pure carbon, carboxylated or Si-doped nanotubes. All investigations were done using computational first principles simulations based on the density functional theory using the SIESTA code. Firstly, we show that carbon nanotubes with single vacancies are highly reactive centers, which can be used as adsorbing sites for selected substances to form covalent bonds on surface. This feature is used to investigate the possibility of forming Si-doped carbon nanotube, analyzing possible energetic barriers and observing the steps of the structural rearrangement to the complete stabilization. The effect of the transversal electric field applied on carbon nanotubes was also investigated. The applied field has a remarkable influence on electronic structure of the semiconductor carbon nanotubes, leading to a band gap decreasing which is dependent on the field intensity and nanotube radius, including a possible semiconductormetal transition. It is also observed that the electric field induces electric polarization and a comparison between semiconductor and metal tubes is presented. In the same way, the action of transversal electric fields on semiconductor and metallic carbon nanotubes functionalized with carboxylic group was estimated. We observe that the presence of carboxyl in the nanotube surface modifies the response to the electric field, leading to considerable alterations on the electronic structure of the original system, such as energy bands, inducing an electric polarization and charge transfers between the adsorbed molecules and the carbon nanotube. Therefore, we also study the electric fields action on carboxylated Si-doped carbon nanotubes. The electronic and structural properties of these systems are analyzed and the results discussed.